The Identification and Quantification of the Positional Isomers of Dimethylbipyridine by Ion Mobility Mass Spectrometry Analysis of Their Gas Phase Complexes - Peng, Xiaopeng; Du, Jianglong; Chen, Long; Ye, Keqi; Ye, Jiacheng; Yan, Yinghua; Ding, Chuan‐Fan (Rapid communications in mass spectrometry, 2025)
ABSTRACT Rationale Dimethylbipyridine (DMDP) serves as a versatile industrial intermediate, with methyl substitutions at distinct positions tailored for varied applications, including the synthesis of DNA reagents and proton receptors. However, the pronounced structural and chemical similarities among its isomers underscore the critical need for an effective method to achieve their quantification and precise identification. Methods This study developed a straightforward, swift, and effective approach for the identification and quantification of two dimethylbipyridine positional isomers, namely, 6,6′‐dimethyl‐2,2′‐bipyridine and 4,4′‐dimethyl‐2,2′‐bipyridine based on the analysis of ion mobility spectrometry (IMS) of their cyclodextrin complex ion in gas phase. Moreover, their spatial conformations and cross sections were simulated by theoretical calculations. Results The complex associated with γ‐CD exhibited superior separation, achieving an Rp‐p of 0.823. And the theoretical computational simulation results are in good alignment with the experimental results, with a computed error value of less than 12.02%. Additionally, the relative quantification of the two DMDP isomers in a mixed solution was examined, yielding very well linear correlation coefficients (R2 > 0.99). Conclusion This study presents a highly promising method for the identification and quantification of two positional isomers of dimethylbipyridine (DMDP). Compared to conventional analytical methods such as HPLC, this approach offers advantages of simplicity, speed, and the elimination of chemical derivatization. It provides a novel perspective for the identification of DMDP isomers in chemical research and industrial applications.